1975
DOI: 10.1128/aac.7.6.874
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Additive Effect of Polymyxin B and Rifampin Against Serratia marcescens

Abstract: The combination of polymyxin B and rifampin resulted in an additive effect against all 12 clinical isolates of Serratia marcescens examined, including multiple-drug-resistant isolates.Very recently, Perez Urena et al. (5) demonstrated that the combination of rifampin and polymyxin B was synergistically effective against all strains of Proteus vulgaris, P. mirabilis, and Pseudomonas aeruginosa examined. As we had previously encountered several clinical isolates of Serratia marcescens (bacteriocin type 18) that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
41
0

Year Published

1977
1977
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 8 publications
3
41
0
Order By: Relevance
“…The present study confirns previous reports of polymyxin B and rifampin synergy against Serratia (12,14) and extends those observations by demonstrating the efficacy of polymyxin B and rifampin in serious Serratia infections. Three of the four patients who failed to respond to polymyxin B and rifampin had severe underlying illnesses, an established risk factor in the treatment of gram-negative bacillary infections (6).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The present study confirns previous reports of polymyxin B and rifampin synergy against Serratia (12,14) and extends those observations by demonstrating the efficacy of polymyxin B and rifampin in serious Serratia infections. Three of the four patients who failed to respond to polymyxin B and rifampin had severe underlying illnesses, an established risk factor in the treatment of gram-negative bacillary infections (6).…”
Section: Discussionsupporting
confidence: 75%
“…An endemic involving multiresistant Serratia at the Little Rock Veterans Administration Hospital (LRVAH) necessitated development of a novel therapeutic regimen. Polymyxin B and rifampin are synergistic in vitro for this species (12,14) but have not been used together in patients. This study was consequently undertaken to evaluate the extent of antibiotic resistance among Serratia at LRVAH, to determine their susceptibility to polymyxin B and rifampin, and to assess the efficacy and toxicity of therapy with polymyxin B and rifampin in patients seriously ill with infections due to multiresistant Serratia.…”
mentioning
confidence: 99%
“…During the course of our investigations concerning the susceptibility of clinical isolates of Serrana marcescens, an opportunistic-pathogenic microorganism of considerable nosocomial significance, to the bacteri cidal activity of human serum, it was observed that so-called 'promptly serum-sensitive' (PS) strains were killed within minutes, whereas 'delayed serum-sensitive' (DS) isolates were killed only after several hours of in cubation [22], Chelation of fresh human serum with 0.01 m of magne sium ions (Mg) plus 0.01 M of ethylene glycol tetraacetic acid (EGTA), a procedure known to render the classical pathway of human complement activation nonfunctional [4,6], prevented 'prompt' killing activity. The formerly PS isolates, including Escherichia coli control strain C, were now killed only after extended incubation [23].…”
Section: Introductionmentioning
confidence: 99%
“…Several agar diffusion methods are also described (7,9,12). Microdilution methods have been described for determining synergy (3,5,6,15,16). Two methods (15,16) involve dilution of both drugs before pipetting each into the microdilution plate.…”
mentioning
confidence: 99%
“…Microdilution methods have been described for determining synergy (3,5,6,15,16). Two methods (15,16) involve dilution of both drugs before pipetting each into the microdilution plate. The method of Kluge et al (6) requires diluting one drug in the microdilution plate, then adding the second drug (already diluted) to the wells containing the first drug.…”
mentioning
confidence: 99%